2010
DOI: 10.1293/tox.23.25
|View full text |Cite
|
Sign up to set email alerts
|

N,N'-Bis(2-chloroethyl)- N-nitrosourea (BCNU)-induced Apoptosis of Neural Progenitor Cells in the Developing Fetal Rat Brain

Abstract: N,N’-bis(2-chloroethyl)-N-nitrosourea (BCNU) is one of the major drugs used in chemotherapy against malignant gliomas due to its effects, such as induction of bifunctional alkylation of DNA and formation of interstrand DNA cross-linkages, and induces cortical malformations in the fetal and neonatal rat brain. In this study, pregnant rats were treated with 7.5 mg/kg of BCNU on gestational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…These adducts can further lead to single/double‐strand breaks, sister chromatid exchange and chromosome aberrations 9–11. A number of in vivo and in vitro experiments of the anticancer mechanism of CENUs indicated that the covalent crosslinks between G–C complimentary base pair represented the most important types of DNA damage involved in the anticancer process 8, 12–19. The formation of G–C crosslinks with an ethidene was proposed to prevent DNA base pair separation and to impede DNA replication, which could result in DNA double‐strand breaks and further led to apoptosis of cancer cells 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adducts can further lead to single/double‐strand breaks, sister chromatid exchange and chromosome aberrations 9–11. A number of in vivo and in vitro experiments of the anticancer mechanism of CENUs indicated that the covalent crosslinks between G–C complimentary base pair represented the most important types of DNA damage involved in the anticancer process 8, 12–19. The formation of G–C crosslinks with an ethidene was proposed to prevent DNA base pair separation and to impede DNA replication, which could result in DNA double‐strand breaks and further led to apoptosis of cancer cells 15.…”
Section: Introductionmentioning
confidence: 99%
“…A number of in vivo and in vitro experiments of the anticancer mechanism of CENUs indicated that the covalent crosslinks between G–C complimentary base pair represented the most important types of DNA damage involved in the anticancer process 8, 12–19. The formation of G–C crosslinks with an ethidene was proposed to prevent DNA base pair separation and to impede DNA replication, which could result in DNA double‐strand breaks and further led to apoptosis of cancer cells 15. Fischhaber et al16 performed a quantitative analysis of BCNU‐induced dG–dC crosslinks in synthesized oligonucleotides with various sequences using high‐performance liquid chromatography‐tandem mass spectrometry (HPLC‐MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that DNA ISC were the most important type of DNA modification leading to cytotoxicity by CENUs. This is because such DNA modifications prevented the separation of DNA double strands in the replication process . Bodell et al compared the levels of DNA alkylation products in human glioma cell lines after treatment with 3 H‐CENUs using high‐performance liquid chromatography (HPLC).…”
mentioning
confidence: 99%
“…ICLs are extremely toxic to cells since they prevent the separation of the two strands of a DNA double helix for cellular processes, such as replication and transcription, by coordinating chemical reactions with bases on opposing strands [4]. The formation of ICLs between complementary base pair is supposed to be the critical step for the anticancer activity of CENUs [5]. Zhao's group found that the ICLs between the N 1 atom of guanine and the N 3 atom of the complementary cytosine through an ethylene is theoretically determined to be the main crosslinking damage in the reactions of DNA and CENUs [6].…”
Section: Introductionmentioning
confidence: 99%